Following in Footsteps or Marching Alone? How Institutional Differences Influence Renewable Energy Policy - PARINANDI, SRINIVAS (University of Michigan Press, 2023)
In recent years, the federal government's increasing inability to address major societal challenges has arguably hampered America's commitment to renewable energy initiatives. Individual U.S. states have stepped into this void and adopted their own policies, leading some to believe that the states can propel America's renewable energy industry forward. However, we know little about how legislative and regulatory dynamics within America's states might accelerate or hinder renewable energy policy creation. In Following in Footsteps or Marching Alone?, Srinivas Parinandi explores how states have devised their own novel policies, and how the political workings of legislatures and public utilities commissions have impacted state renewable energy policy design. Through the meticulous study of nearly three decades of state-level renewable energy policy-making, he finds that their creation is primarily driven by legislatures, and that ideologically liberal legislatures largely push the envelope. The book suggests that having a predominantly state-driven renewable energy effort can lead to uneven and patchwork-based policy development outcomes, and a possible solution is to try to more successfully federalize these issues. Parinandi urges readers, scholars, and policy practitioners to consider whether a state-led effort is adequate enough to handle the task of building momentum for renewable energy in one of the world's largest electricity markets.